Conformación de un equipo de investigadores: una experiencia concreta - Laura Esquivel-Segura; Gina Induni-Alfaro; Vera Madrigal-Rojas; Zulay Pereira-Pérez; José Solano-Alpízar; Willy Umaña-Fernández (Universidad Nacional, Costa Rica, 2004)
First of two articles describing the experience shared by a group of CIDE (School of Education at UNA, Costa Rica) scholars in conforming a team of researchers. The first points out not only how the idea was originated but also the different stages it went through and the strategies used to stimulated it. In addition, some suggestions are given so that future researches may benefit from them when facing similar tasks. The second article defines the methodological strategy adopted by the team and the constructive process that was followed to reach such methodological approach.